BMI growth trajectory from birth to 5 years and its sex-specific association with prepregnant BMI and gestational weight gain - Xie, Jinting; Han, Yan; Peng, Lei; Zhang, Jingjing; Gong, Xiangjun; Du, Yan; Ren, Xiangmei; Zhou, Li; Li, Yuanhong; Zeng, Ping; Shao, Jihong (Frontiers in Nutrition, 2023)
Objective: To identify latent body mass index (BMI) z-score trajectories of children from birth to five years old and evaluate their sex-specific association with prepregnant BMI (pp-BMI) and gestational weight gain (GWG). Methods: This was a retrospective longitudinal cohort study performed in China. Three distinct BMI-z trajectories from birth to age 5 years were determined for both genders by using the latent class growth modeling (LCGM). Logistic regression model was used to assess the associations of maternal pp-BMI and GWG with childhood BMI-z growth trajectories. Results: Excessive GWG increased the risks of children falling into high-BMI-z trajectory relative to adequate GWG (OR=2.04, 95%CI:1.29, 3.20) in boys; girls born to mothers with pre-pregnancy underweight had a higher risk of low-BMI-z trajectory than girls born to mothers with pre-pregnancy adequate weight (OR=1.85, 95%CI: 1.22, 2.79). Conclusions: BMI-z growth trajectories of children from 0 to 5 years of age have population heterogeneity. Pp-BMI and GWG are associated with child BMI-z trajectories. It is necessary to monitor weight status before and during pregnancy to promote maternal and child health.